Beginning Xamarin Development for the Mac : create iOS, watchOS, and Apple tvOS apps with Xamarin.iOS and Visual Studio for Mac /: create iOS, watchOS, and Apple tvOS apps with Xamarin.iOS and Visual Studio for Mac. (2018) - Borycki, Dawid
No abstract available